2014
DOI: 10.5005/jp-journals-10005-1266
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid Cystic Carcinoma of Child: A Rare Case

Abstract: ABSTRACT%Adenoid cystic carcinoma (ACC) is the second most common malignant tumor affecting both major and minor salivary glands. Clinically, it is a slowly growing tumor with high propensity for local invasion, recurrence and distant metastasis. It is predominantly seen in the ffith and sixth decades of life. Here, we report a rare case of ACC affecting the right maxilla of a 12-year-old girl.How to cite this article: Mathai M, Sherubin JE, Agnihotri PG, Sangeetha GS. Adenoid Cystic Carcinoma of Child: A Rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…ACC occurred in children and young adults aged ≤20 years is rare. To date, only few case series have been published on children and young adult ACC, and most of these have been reported as case reports (De Campora et al, 1987; Javadi et al, 2002; Locati et al, 2017; Mathai et al, 2014; Murao, 1980; Nassar & Sawczyn, 2013; Varan et al, 2014; Xu, Aneja, et al, 2017a). In the present study, we reported 12 cases of children and young adult ACC and analyzed the clinicopathological characteristics, immunohistochemical profiles, and molecular alterations of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…ACC occurred in children and young adults aged ≤20 years is rare. To date, only few case series have been published on children and young adult ACC, and most of these have been reported as case reports (De Campora et al, 1987; Javadi et al, 2002; Locati et al, 2017; Mathai et al, 2014; Murao, 1980; Nassar & Sawczyn, 2013; Varan et al, 2014; Xu, Aneja, et al, 2017a). In the present study, we reported 12 cases of children and young adult ACC and analyzed the clinicopathological characteristics, immunohistochemical profiles, and molecular alterations of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Perineural invasion is the pathognomonic factor responsible for high rate of local recurrence. Lymph node involvement is rare and is usually caused by contiguous spread rather than lymphatic permeation or embolization [3].…”
Section: Discussionmentioning
confidence: 99%